A History of Egypt from the End of the Neolithic Period to the Death of Cleopatra VII B.C. 30 (Routledge Revivals) - Budge, E. A. Wallis, author.
1 online resource (272 pages)
Keywords: Sir E. A. Wallis Budge (1857-1934) was Keeper of the British Museum’s department of oriental antiquities from 1894 until his retirement in 1924. Carrying out many missions to Egypt in search of ancient objects, Budge was hugely successful in collecting papyri, statues and other artefacts for the trustees of the British Museum: numbering into the thousands and of great cultural and historical significance. Budge published well over 100 monographs, which shaped the development of future scholarship and are still of great academic value today, dealing with subjects such as Egyptian religion, history and literature. This volume, first published in 1902, is the seventh of eight volumes by Budge dealing with different periods in the history of Egypt. The narrative begins with the reign of Uah-ab-Rā, a king of the XXVIth Dynasty, and ends with that of Ptolemy IV. A period of increasing national prosperity, the influence of external influences can be seen during these years, which Budge argues paved the way for the advent of Christianity. This is a fascinating and important work, which is still of great value to those interested in Egyptology and archaeology.